ASSESSING COMPETENCY-BASED FRAMEWORK FOR LINGUIST TRAINING IN THE UK: BENEFITS FOR UKRAINE - Dorofeyeva, Olena; Lapshyna, Olha (The Modern Higher Education Review, 2024)
This article explores the evolution of competency-based education in the UK, particularly its implications for professional training of linguists. It begins by highlighting the necessity of enhancing students’ cognitive abilities to foster engagement in shaping their educational and social environments. The article examines the shift from traditional academic evaluations to competency assessments promoted by the Bologna Process, emphasizing the need for interdisciplinary standards in education. It provides a historical overview of the UK’s competency-based approach, tracing its origins in the 1980s and the development of National Vocational Qualifications (NVQs) and national occupational standards. These frameworks, established through stakeholder collaboration, ensure that graduates possess the necessary competencies for their professional roles. The article further discusses the integration of digital skills and adaptability into competency frameworks, reflecting the demands of a rapidly changing labour market. By analysing the UK experience, this study offers insights into enhancing the training of future linguists in Ukraine, aligning educational outcomes with real-world demands while maintaining high standards of professional competency.